Memory Recall for High Reward Value Items Correlates With Individual Differences in White Matter Pathways Associated With Reward Processing and Fronto-Temporal Communication - Reggente, Nicco; Cohen, Michael S.; Zheng, Zhong S.; Castel, Alan D.; Knowlton, Barbara J.; Rissman, Jesse (Frontiers in Human Neuroscience, 2018)
When given a long list of items to remember, people typically prioritize the memorization of the most valuable items. Prior neuroimaging studies have found that cues denoting the presence of high value items can lead to increased activation of the mesolimbic dopamingeric reward circuit, including the nucleus accumbens (NAcc) and ventral tegmental area (VTA), which in turn results in up-regulation of medial temporal lobe encoding processes and better memory for the high value items. Value cues may also trigger the use of elaborative semantic encoding strategies which depend on interactions between frontal and temporal lobe structures. We used diffusion tensor imaging (DTI) to examine whether individual differences in anatomical connectivity within these circuits are associated with value-induced modulation of memory. DTI data were collected from 19 adults who also participated in an fMRI study involving a value-directed memory task. In this task, subjects encoded words with arbitrarily assigned point values and completed free recall tests after each list, showing improved recall performance for high value items. Motivated by our prior fMRI finding of increased recruitment of left-lateralized semantic network regions during the encoding of high value words (Cohen et al., 2014), we predicted that the robustness of the white matter pathways connecting the ventrolateral prefrontal cortex with the temporal lobe might be a determinant of recall performance for high value items. We found that the mean fractional anisotropy of each subject's left uncinate fasciculus, a fronto-temporal fiber bundle thought to play a critical role in semantic processing, correlated with the mean number of high value, but not low value, words that subjects recalled. Given prior findings on reward-induced modulation of memory, we also used probabilistic tractography to examine the white matter pathway that links the NAcc to the VTA. We found that the number of fibers projecting from left NAcc to VTA was reliably correlated with subjects' selectivity index, a behavioral measure reflecting the degree to which recall performance was impacted by item value. Together, these findings help to elucidate the neuroanatomical pathways that support verbal memory encoding and its modulation by value.